Pendidikan Kewarganegaraan dalam Kehidupan Berbangsa dan Bernegara - Muhamad Farhan Nurdiansyah; Dinie Anggraeni Dewi (Civiliza Publishing, 2021)
The purpose of this study is to find the role of civic education in guiding every citizen in carrying out his life. This shows that the existence of Citizenship Education has an important role in shaping the personal character of the younger generation. Our learning so far has been verbalistic and oriented solely to mastering the content of civic education subjects. Observations of daily learning practices show that learning is focused so that students master the information contained in the subject matter and then evaluate how far that mastery is achieved by students. It is as if learning aims to master the content of these subjects. How the teaching material is related to everyday life and how this material can be used to solve life's problems has received less attention.